Interlinear Glossed Text for Saami, Inari - Lewis, William (California State University, Fresno, ODIN project, 2007)
A listing of Web resources containing Interlinear Glossed Text for the language Saami, Inari: 2 document(s), 8 instance(s) of interlinear text.